Extraction, and Characterization of Carotenoids from 11 Allelopathic Plant Species as Potential Halal Food Colorants and Active Pharmaceutical Ingredients - Rashidi Othman; Razanah Ramya; Muhammad Azzubair Azeman; Norazian Mohd. Hassan; Suhair Kamoona (Journal of Pharmacy and Nutrition Sciences, 2020)
Carotenoids are a class of natural product compound that are currently being used as colouring agents and widely used in food industry. Carotenoids are bioactive pigments obtained mainly from plants through dietary intake. They possess good features in terms of dietary supplement, food colourant, and polymer stabiliser. The presence of 4 main carotenoids, which are β-carotene, zeaxanthin, lutein, and violaxanthin, were determined in 4 classes of allelopathic plant groups namely trees, ferns, grasses and herbaceous plants. This research aims to explore the carotenoid’s content and composition in 11 allelopathic species by HPLC analysis. A. auriculiformis (tree) was found to have the highest total carotenoid concentration (146.36 µg/g DW) that was substantially higher than all other species tested whereas the lowest total carotenoid concentration was found in S. palustris (fern) (3.76 µg/g DW). Lutein and β-carotene were detected highest in A. auriculiformis (tree), with 1024 ± 25.5 µg/g DW and 37.55 ± 3.16 µg/g DW, respectively. Violaxanthin and zeaxanthin were found substantially highest in M. cajuputi (tree) (5.02 ± 0.5 µg/g DW) and S. palustris (fern) (5.88 ± 0.19µg/g DW), respectively.